Evaluación de la calidad del agua en la quebrada Zaragosa del distrito de Nauta en Loreto, 2024 - Ruiz Laulate, Oty Zelenita (2025)
Water quality is an issue due to its multiple uses, including human consumption. The objective was to assess the water quality of the Zaragosa creek, located in the district of Nauta, Loreto. The methodology used was the Environmental Quality Index for Surface Water Resources (ICARHS), which consists of three stages: determining the scope of the study, collecting information, and calculating the ICARHS. Additionally, 50 surveys were conducted with visitors, bathers, and residents of the area. The results indicate that the pH varied between 6.26 and 8.54, the true color ranged from 8 to 150 Pt/Co, conductivity was between 14.8 and 50.2 µS/cm, and total suspended solids were found to be between 5 and 50 mg/L. No oils, fats, lead, or nitrates were detected. Dissolved oxygen values ranged from 2.30 to 8.40 mg/L. Zinc had a concentration of 0.01 mg/L, phosphorus ranged from 0.06 to 0.96 mg/L, and coliforms varied between 4600 and 6800 NMP/100 ml. It is important to note that pH, true color, dissolved oxygen, phosphorus, and coliforms exceed the levels set by the Environmental Quality Standard (ECA) for water. Identified sources of contamination include wastewater discharges from households, and both ambulatory and fixed commerce. Surveys revealed that 8% of the population reports gastrointestinal illnesses, 10% dermatitis, and 4% respiratory issues. Finally, the water quality received an ICARHS value of 82.8. In conclusion, the water quality can be classified as "good.".